1992
DOI: 10.1021/bi00132a028
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic electron-transfer reactions in the green sulfur bacterium Chlorobium vibrioforme: Evidence for the functional involvement of iron-sulfur redox centers on the acceptor side of the reaction center

Abstract: The green sulfur bacterium Chlorobium vibrioforme was cultured in the presence of ethylene to selectively inhibit the synthesis of the chlorosome antenna BChl d. Use of these cells as starting material simplified the isolation of a photoactive antenna-depleted membrane fraction without the use of high concentrations of detergents. The preparation had a BChl alpha/P840 of 50, and the spectral properties were similar to those of preparations isolated from cells grown with a normal complement of chlorosomes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 43 publications
4
50
0
Order By: Relevance
“…Similar spectra have been observed in C. limicola f. sp. thiosulfatophilum (Nitschke et al, 1990;Feiler et al, 1992;Oh-oka et al, 1993) and C. vibrioforme (Miller et al, 1992) and C. tepedum (Kusumoto et al, 1994). In analogy with PS I, these resonances (termed signal 111) are proposed to represent an interaction spectrum from two spin coupled iron-sulfur clusters within the same protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar spectra have been observed in C. limicola f. sp. thiosulfatophilum (Nitschke et al, 1990;Feiler et al, 1992;Oh-oka et al, 1993) and C. vibrioforme (Miller et al, 1992) and C. tepedum (Kusumoto et al, 1994). In analogy with PS I, these resonances (termed signal 111) are proposed to represent an interaction spectrum from two spin coupled iron-sulfur clusters within the same protein.…”
Section: Resultsmentioning
confidence: 99%
“…In two landmark studies, Knaff and Malkin (1976) identified a low potential iron-sulfur center with a midpoint potential of approximately -550 mV in chromatophores from C. limicola f. thiosulfatophilum, and Jennings and Evans (1977) described the irreversible, light-induced reduction of a component with a midpoint potential of approximately -550 mV in a preparation from the same organism. Typically, a set of resonances with a trough at about g = 1.85 are seen on illumination at cryogenic temperatures in C. limicola f. thiosulfatophilum (Jennings and Evans, 1977;Nitschke et al, 1990;Feiler et al, 1992;Oh-oka et al, 1993), C. vibrioforme (Kjcer et al, 1994) and C. tepidum (Kusumoto et al, 1994), and a spectrum with mid-field and high-field g values of 1.89 and 1.91 is observed when samples are frozen in light to photoaccumulate more than one electron in C. limicola f. thiosulfatophilum (Nitschke et al, 1990;Feiler et al, 1992;Oh-oka et al, 1993), C. vibrioforme (Kjcer et al, 1994;Miller et al, 1992) and C. tepidum (Kusumoto et al, 1994). A similar spectrum is found in chemically reduced reaction centers of C. tepidum (Kusumoto et al, 1994).…”
mentioning
confidence: 99%
“…(i) A pair of PscA core protein, that shows homology in amino acid sequences to both of PsaA and PsaB core proteins of PS I, seem to make up the so-called 'homodimer' RC in contrast to the asymmetric 'heterodimer' RC of other photosynthetic organisms [1]. (ii) The RC contains three iron-sulfur clusters that resemble Fx, FA and F B clusters in PSI RC [2][3][4][5][6]. The binding motifs for F x-and FAIFB-like clusters reside in the PscA core and the PscB proteins, respectively, in C. limicola [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for the secondary acceptor quinone is still scarce. Photo-oxidized P840 is reduced by cytochrome c [3,5,10,11]. The gene encoding the cytochrome c identified in C. vihrioforme has a single heine binding moiety in a conserved motif, Cys-X-X-Cys-His [8].…”
Section: Introductionmentioning
confidence: 99%
“…Such a spectrum can be obtained for PSI, but is only observed in PSI1 or purple bacteria if the non-heme iron is removed. The observation of an electron spin polarized signal [8,10], and indirect evidence suggesting that the triplet of P840' is affected by conditions that could lead to double reduction of a quinone [7] suggest the presence of an 'AI' quinone acceptor in C thiosulphatophilum. However, the presence of a quinone acceptor in Heliobacteriaceae is disputed [ 111.…”
Section: Introductionmentioning
confidence: 99%